Antibacterial activity of baicalein against Aeromonas hydrophila: in vitro and in vivo evaluation - Qiu, Reng; Li, Jun; Jiang, Changjun; Yu, Yang; Li, Dandan; Xie, Xuehan; Lei, Yang; Yao, Lunguang (Frontiers in Microbiology, 2025)
IntroductionAeromonas hydrophila (AH) is a pathogenic bacterium commonly found in aquatic organisms, particularly in fish products. Baicalein, a bioactive flavonoid derived from traditional Chinese herbal medicine, possesses a wide range of pharmacological properties, including anticancer, antibacterial, antiviral, antioxidant, hepatoprotective, and anti-inflammatory effects.MethodsIn vitro, the Oxford cup method was employed to assess the antibacterial activity of baicalein, while the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined using the microtiter broth dilution technique. Biofilm formation and bacterial motility were evaluated through the crystal violet assay and swimming assay, respectively. The impact of baicalein on bacterial membrane permeability and morphology was observed using the Live/Dead BacLight kit and transmission electron microscopy. In vivo, grass carp were used as the model organism to evaluate the effect of baicalein on AH proliferation, while the expression of pro-inflammatory cytokines and antioxidant factors was quantified by qRT-PCR.ResultsThis study demonstrated the antibacterial activity of baicalein against AH infection. Baicalein exhibited bacteriostatic effects in vitro, with an MIC of 40 μg/mL and an MBC of 80 μg/mL. Time-kill assays confirmed its bactericidal properties. Additionally, baicalein inhibited biofilm formation and reduced bacterial motility. The antibacterial mechanism of baicalein involved increased membrane permeability and structural disruption of AH cells. In vivo studies in grass carp revealed a dose-dependent reduction in AH burden following baicalein administration. Moreover, baicalein suppressed the expression of pro-inflammatory cytokines, including interleukin-1β (IL-1β), interleukin-8 (IL-8), and tumor necrosis factor-α (TNF-α), while enhancing the expression of antioxidant-related genes, such as catalase (CAT), glutathione reductase (GR), and superoxide dismutase (SOD). These findings indicate that the antibacterial and anti-inflammatory effects of baicalein contribute to its protective role against AH infection in vivo.DiscussionBaicalein effectively inhibits the proliferation of AH both in vitro and in vivo, highlighting its potential as a promising pharmacotherapeutic agent for the prevention of AH infections in fish.